Influence of entrepreneurship support programs on nascent entrepreneurial intention among university students in China - Liao, Shiyan; Javed, Hasnain; Sun, Lixin; Abbas, Muzaffar (Frontiers in Psychology, 2022)
This study aimed to investigate the impact of entrepreneurial educational support, entrepreneurial activities support, and entrepreneurial commercialization support on the nascent entrepreneurial intention with mediating roles of entrepreneurial self-efficacy and opportunity recognition and moderating effect of meaning in life. Data were gathered using a survey questionnaire from the 868 management, engineering, technical, and vocational institute students of China. The nascent entrepreneurial intention model was analyzed using the partial least squares structural equation modeling through Smart-PLS software. The findings of the study reveal that entrepreneurial educational support, entrepreneurial activities support, and entrepreneurial commercialization support have a positive effect on nascent entrepreneurial intention. Meanwhile, results indicate that entrepreneurial self-efficacy and opportunity recognition partially mediates in the relationship between entrepreneurship support programs and nascent entrepreneurial intention. Furthermore, the relationship between entrepreneurial self-efficacy and the nascent entrepreneurial intention was insignificantly influenced by meaning in life, and the relationship between opportunity recognition and the nascent entrepreneurial intention was significantly moderated by meaning in life. Lastly, implications and limitations were also discussed in this article.